The cooperative paradigm in the management and direction of coperative organizations (Dissertare, 2017)
The present work is an ongoing research that aims to analyze the correspondence between the management and administrative structure of large cooperative organizations and the application of the values ​​and principles contemplated in the cooperative paradigm, in order to propose mechanisms that favor harmonization of these two models. The research has a quantitative nature and its object of study is a group of 18 agricultural cooperatives based in the Province of Entre Ríos, Argentina, which represent almost 18% of the commercialization of the agricultural production of the province, whose seniority is greater to sixty years The survey and the review of documents such as: reports and balance sheets of the last ten years were used as data collection techniques; also, minutes of assemblies and council meetings; as well as, constitutive acts and other historical materials available. Descriptive statistics was used to analyze the information. The study concludes that large cooperatives have generated managerial and bureaucratic structures that have distanced them from associates and cooperative values, in favor of profitability.
Keywords: paradigm; cooperatives; cooperative education; cooperative management